Assessment of temperament traits of white-lipped (Tayassu pecari) and collared peccaries (Pecari tajacu) during handling in a farmed environment - Nogueira, S. S.C.; Macêdo, J. F.; Sant'Anna, A. C. [UNESP]; Nogueira-Filho, S. L.G.; Paranhos Da Costa, M. J.R. [UNESP] (Cambridge University Press (CUP), 2015)
White-lipped (Tayassu pecari) and collared (Pecari tajacu) peccaries can be farmed as an alternative to subsistence hunting in Neotropical countries. The animals often show high reactivity to handling, usually involving capture with a net, which is a cause for concern because it poses risks to both animals' and keepers' welfare. We aimed to assess the temperament of both peccary species, evaluating animals' reactions during handling, providing an emotional indicator and a new animal selection criterion for peccary farms. Three indicators were used to assess the temperament of 17 white-lipped and 19 collared peccaries: qualitative behaviour assessment (QBA, by using 12 behavioural adjectives); time to drive each animal through a corridor into a chute (TD, s); and flight speed (FS, m s-1). A Principal Components Analysis was performed for the QBA data to define a temperament index (TI). White-lipped peccaries showed TI scores associated with worse temperament traits than collared peccaries. White-lipped peccaries showed higher TD and FS means than collared peccaries. We found a correlation between TD and FS, but not between TD and TI, nor between FS and TI. The lack of correlation between all temperament indicators occurred, probably, because they measure different aspects of peccaries' reactions toward humans and the farm environment during handling. A wide phenotypic variability was found among individuals within both species' populations. The results provide an opportunity to address the role of temperament assessment, improving handling procedures and exploring the possibility of including temperament as a selection criterion in captive breeding programmes.
Keywords: Animal welfare; Domestication; Handling; Peccary; Reactivity; Wildlife farming